Distribusi Frekuensi-Magnitudo Gempa Mikro Akibat Aktivitas Stimulasi Hidrolik pada Lapangan Panas Bumi Tipe Hot Dry Rock (HDR) - Nanda Hanyfa Maulida; Muhamad Firdaus Al Hakim; Hesti; Suharno (Jurnal Teknik dan Teknologi Indonesia, 2023)
A series of hydraulic stimulations were conducted to enhance permeability and increase the production of hot fluid in a Hot Dry Rock (HDR) geothermal field. The stimulation involved injecting water into the hot rock, inducing hydraulic fracturing and resulting in over 2000 micro-earthquake events within the field. Utilizing existing microearthquake data, an analysis of the microearthquake distribution was performed, along with calculating the gradient of the frequency-magnitude distribution of microearthquakes (b-value) to assess the heterogeneity conditions induced by high pore pressure. The hypocenter distribution is centered around injection and production locations, displaying a trend that aligns with the main structure trending southwest to northeast. The mapping of b-values indicates elevated values in the hydraulic stimulation area, believed to be associated with increased pore pressure resulting from the higher fluid volume in that region. Moreover, high b-values were identified beneath the production area, suggesting the potential migration of injection fluid from the hydraulic stimulation process.